Training aircraft selection for department of flight training in fuzzy environment - Torğul, Belkız; Demiralay, Enes; Paksoy, Turan (Decision Making: Applications in Management and Engineering, 2022)
Modern aviation has gained an important place in the transportation sector since the Montgolfier brothers designed the air balloon. Aircraft are fast becoming a key instrument in passenger and cargo transportation. The last two decades have seen a growing trend towards the use of aircraft as transportation tools. International aircraft companies report that new aircraft orders are increasing every year. However, there is a lack of routes because of the insufficient number of pilots. Therefore, the increase in usage of aircraft has been limited. To respond to this increase in Turkey, it indicates a rise in the number of flight academies. Flight academies have emerged as powerful and expensive platforms for flight training. In the new global economy, the aircraft selection problem has become a central issue for Flight Training Departments, which is planned to open in government universities. In this study, an approach based on the fuzzy BWM method is proposed to select more suitable training aircraft in government universities. Criterion weights and alternative aircraft rankings were determined using the fuzzy BWM method. Afterward, a mathematical model was developed to calculate how many aircraft we need to buy under certain constraints. Necmettin Erbakan University, which wants to train new and qualified pilots, needs training aircraft, which is the most critical factor, and trainers that can provide pilot training. A case study of training aircraft selection was conducted for the Necmettin Erbakan University Department of Flight Training.